2002
DOI: 10.1007/bf03190403
|View full text |Cite
|
Sign up to set email alerts
|

Distribution and elimination characteristics of111In-DTPA-D-Phe1-octreotide and111In-DTPA-L-Phe1-octreotide in rats

Abstract: The present study compares distribution and elimination characteristics of 111In-DTPA-D-Phe1-octreotide and 111In-DTPA-L-Phe1-octreotide in rats and evaluated the effect of the replacement of the terminal L-phenylalanine by D-phenylalanine on pharmacokinetic profiles of the radiolabelled peptides. Both agents exhibited rapid radioactivity clearance from the blood and most organs and tissues with no systematic and significant differences in activity accumulation. The long-term retention and high radioactivity c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 7 publications
1
2
0
Order By: Relevance
“…Because this renal excretion process is indirectly related to the rate of binding to plasma proteins, the higher clearance of 111 In-DOTA-TATE in the perfused rat kidney was primarily attributed to the lower degree of binding to plasma proteins found in the applied perfusate. No signifi cant presentation of low-molecular metabolites of 111 In-DOTA-TATE or 111 In-DOTA-NOC in the urine of the perfused kidney confi rmed similar observations found with other radiolabeled somatostatin analogs [26,27].…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Because this renal excretion process is indirectly related to the rate of binding to plasma proteins, the higher clearance of 111 In-DOTA-TATE in the perfused rat kidney was primarily attributed to the lower degree of binding to plasma proteins found in the applied perfusate. No signifi cant presentation of low-molecular metabolites of 111 In-DOTA-TATE or 111 In-DOTA-NOC in the urine of the perfused kidney confi rmed similar observations found with other radiolabeled somatostatin analogs [26,27].…”
Section: Discussionsupporting
confidence: 85%
“…Experimental elimination studies have shown that a majority of radiolabeled somatostatin analogs are excreted via urine, mostly in an intact form [7,26,27]. However, the number of studies on renal handling and transport mechanisms of these compounds is still limited.…”
Section: Discussionmentioning
confidence: 98%
“…The faster renal washout observed in the case of 99m Tc-DOMA-AATE and 99m Tc-DOMA-PATE at the longer time intervals (after 2 h post-injection) is reminiscent of its behavior in the experimental tumor and in the physiological SSTR2-positive sites and contrasts with the prolonged residence of 99m Tc-HYNIC-TOC in these tissues. We know from the previous literature that the molecular charges of peptide play an important role in re-absorption of the protein from glomerular filtrate into renal proximal tubular cells (Kopecky et al 2004;Laznickova et al 2002). However, since negatively charged 99m Tc-DOMA/ 99m Tc-HYNIC is attached to these peptides and changed one amino acid that significantly altered the net charges of the resulting octreotide derivative than TOC.…”
Section: Discussionmentioning
confidence: 92%